1998
DOI: 10.1148/radiology.208.3.9722835
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-producing tumor of the pancreas: diagnostic value of diffusion-weighted echo-planar MR imaging.

Abstract: Diffusion-weighted MR imaging can help characterize cystic lesions of the pancreas. Findings-suggestive of viscous fluid in mucin-producing tumors are present on such images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
47
0
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 0 publications
0
47
0
5
Order By: Relevance
“…DW-MRI studies of focal liver masses showed lower apparent diffusion coefficient (ADC) values in malignant masses as compared to benign masses and cysts (17). In another study, DW-MRI showed lower ADC values in mucin-producing tumors of the pancreas and pseudocysts as compared to serous cysts and cerebrospinal fluid (18). This technique was also used to show a significant perfusion contribution to the ADC values in the abdominal organs and hepatic lesions (19).…”
mentioning
confidence: 98%
“…DW-MRI studies of focal liver masses showed lower apparent diffusion coefficient (ADC) values in malignant masses as compared to benign masses and cysts (17). In another study, DW-MRI showed lower ADC values in mucin-producing tumors of the pancreas and pseudocysts as compared to serous cysts and cerebrospinal fluid (18). This technique was also used to show a significant perfusion contribution to the ADC values in the abdominal organs and hepatic lesions (19).…”
mentioning
confidence: 98%
“…DWI is a primary imaging method which is used in the diagnosis of cerebral infarction. Recently, however it has been used to evaluate other organs such as ovaries, pancreas, prostate and breast (5,(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al (9) reported that diffusion-weighted MRI can indicate the presence of mucinous products in the cystic tumor of the pancreas. Mucin is echo-free on sonography, water-attenuating on CT, and shows water signal intensity on T2-weighted MRCP; therefore, intraductal mucin is difficult to detect with conventional noninvasive imaging modalities.…”
Section: Discussionmentioning
confidence: 99%